190k views
18 votes
Solve for the value of x:-

\tt 3(x + 2) - (x - 1) = 17

2 Answers

9 votes

Question:-

Solve for the value of x:-

3(x + 2) - (x - 1) = 17

Answer:-

x = 5

Explanation:-

=> 3(x + 2) - (x - 1) = 17

=> 3x + 6 - x + 1 = 17

=> 3x - x + 6 + 1 = 17 [Simplified]

=> 2x + 7 = 17

=> 2x = 17-7

=> 2x = 10

=> x = 10/2

=> x = 5

User Smittey
by
4.3k points
8 votes

Answer:

x= 5

Explanation:

3(x +2) -(x -1)= 17

Expand:

3(x) +3(2) -x +1= 17

3x +6 -x +1= 17

Simplify:

3x -x +6 +1= 17

2x +7= 17

-7 on both sides of the equation:

2x= 17 -7

2x= 10

Divide both sides by 2:

x= 10 ÷2

x= 5

User Syngularity
by
5.2k points